Ответ:
Пошаговое объяснение:
4) =(√x)' /√(1-x) - 4/√(1-16x²) = -1/(2√x ·√(1-x)) - 4/√(1-16x²)
5) = [ 2· (3x²+5x-1)⁻² ]' = -2·2·(3x²+5x-1)⁻³· (6x+5)= -4·(6x+5)/(3x²+5x-1)³
Запишем уравнение нормали в общем виде
Унор = f(x₀) - (x-x₀) / f'(x₀) ⇔ x₀ =4; f(4) =2·4² -12·4 + 20 = 4
y'(x) = 4x-12; y'(4) = 4·4-12 = 4;
Унор = 4 -(x-4)/4 = -0,25x + 5
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
4) =(√x)' /√(1-x) - 4/√(1-16x²) = -1/(2√x ·√(1-x)) - 4/√(1-16x²)
5) = [ 2· (3x²+5x-1)⁻² ]' = -2·2·(3x²+5x-1)⁻³· (6x+5)= -4·(6x+5)/(3x²+5x-1)³
Запишем уравнение нормали в общем виде
Унор = f(x₀) - (x-x₀) / f'(x₀) ⇔ x₀ =4; f(4) =2·4² -12·4 + 20 = 4
y'(x) = 4x-12; y'(4) = 4·4-12 = 4;
Унор = 4 -(x-4)/4 = -0,25x + 5